Pengelolaan Pariwisata Berbasis Masyarakat di Desa Penglipuran - Adrian Agoes; Sely Gustini; Haikal Alma Nadhira (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2023)
Penglipuran is a village located in Kubu Village, Bangli District, Bangli Regency. Penglipuran Village is a traditional village which has an area of 112 hectares and has 1,028 inhabitants with a total of 280 families. This research is about the management of Penglipuran Village which brings positive aspects to the surrounding community, especially the people who are in the Penglipuran Village area both from an economic, social or cultural perspective. This study uses a descriptive qualitative approach. Data collection was carried out through direct observation, interviews and documentation. The informants in this study are the managers of Penglipuran Village and the surrounding community. The purpose of this study is to find out how Penglipuran Traditional Village is managed. Based on the results of the research, it shows that community involvement in the management of Penglipuran Village has a positive impact on the community and maintains Balinese culture and customs. Community participation is the main support in developing and preserving the existing culture.